Magyarország állam-szomszédsági környezetének átalakulása : 1918-2008 - Hajdú, Zoltán (Közép-Európai Közlemények, 2009)
After the World War, and collapsed of Austro-Hungarian Monarchy in 1918, Hungary turned to be a really independent state in June of 1920, on the 1/3 of former historical territory. The new neighourhood (Austria, Czecho-Slovakia, Romania, Yugoslavia) were on bad terms with Hungary. Between 1938–1941 the state-neighbourhood of Hungary changed very rapidly. Great power (Germany, Soviet Union) neighbours appeared around Hungary, and „old” neighbours (Austria, Czecho-Slovakia, Yugoslavia) disappaered. In 1945 turned to be again a new negihbourhood around Hungary (Austria, Czecho-Slovakia, Soviet Union, Romania, Yugoslavia). After the socialist countries’ systemic changes a new neighbourhood was established around Hungary. She had seven (Austria, Slovakia, Ukraine, Romania, Serbia, Croatia, Slovenia) neighbours.